Sellado dentinario inmediato y Resin coating como técnicas de protección dentinaria en restauraciones indirectas. - Montero Chavarrea, Diego Sebastian (2025)
Immediate Dentin Sealing (IDS) and Resin Coating are dentin sealing techniques primarily indicated in dental preparations for receiving indirect restorations. Both techniques aim to create a hybrid layer between the recently cut dentinal tubules, but one or the other is used depending on the adhesive system to be employed. The purpose of the research is to determine the benefits of using the Immediate Dentin Sealing and Resin Coating techniques as dentin protection methods in dental preparations for indirect restorations. The present research work is of a bibliographic type, where evidence-based dentistry is prioritized through the collection of scientific information from articles, systematic reviews, theses, protocols, practical guides, among others, focused on Dentin Sealing and Resin Coating as dentin protection techniques in indirect restorations using the PRISMA method (Preferred Reporting Items for Systematic reviews and Meta-Analyses). After the analysis, it is concluded that both Immediate Dentin Sealing (IDS) and Resin Coating are completely effective in preventing postoperative sensitivity in patients during and after dental preparation. However, there are notable differences regarding adhesion to restorative materials, with IDS showing the greatest increase in adhesion. It is established that IDS is effective not only when performed with conventional adhesive systems but also when performed with universal adhesive systems containing filler in their composition.